Eating disorders - anorexia as an interdisciplinary problem - Sowińska-Przepiera, Elżbieta; Patalong-Wójcik, Martyna; Andrysiak-Mamos, Elżbieta; Starzyński, Dariusz; Przestalski, Marek; Syrenicz, Anhelli (Journal of Education, Health and Sport, 2019)
Eating disorders are a significant medical and social problem. The most commonly diagnosed eating disorders include anorexia nervosa (AN) and bulimia nervosa, currently classified as behavioral disorders.Anorexia nervosa is a disease consisting in deliberate weight loss and disturbed its image and dysmorphophobia, often coexisting with symptoms of depression and social withdrawal. Understanding the problem of anorexia is not just about food or body mass. Underlying disorders include, among others: emotional problems, the need to define your own identity, a negative image of yourself.AN in women in the general population occurs at a frequency of 0.5-1%, in men 0.05-0.1%, in Poland it ranges from 0.8% -1,8% of the population of girls <18 years old.The etiology of the disease is multifactorial and unclear. Predisposing factors include, among others, genetic factors, personality disorders, specific family patterns (overprotection, entrapment, avoidance of conflicts) and good economic status.AN is a diagnostic challenge, symptomatology is broad, including behavioral changes, psychological and somatic symptoms and specific deviations in biochemical and hormonal tests. The treatment model is multidisciplinary and multi-stage, including: (1) life-saving therapy (prevention of dehydration, dyseectrolytia and wasting), (2) restoration of normal body weight, (3) supportive pharmacotherapy, (4) psychotherapy. The effectiveness of anorexia therapy is unsatisfactory. Anorexia is a mental disorder with the highest mortality rate: after 15-20 years of illness, mortality increases to 19-20%, mainly as a result of cardiovascular complications and suicides.